LINGUOPOETIC FEATURES OF SIMILES IN THE EPIC “ALPOMISH” (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the linguopoetic features of similes in the epic “Alpomish.” It highlights the functions of similes in creating imagery, expressing the inner and outer states of characters, intensifying emotional and expressive effect, and representing national-cultural semantics. The study also analyzes the structural-semantic nature of similes, their extended forms, and their role in epic discourse. As a result, it is shown that similes in the epic “Alpomish” are one of the important linguopoetic devices of epic poetics.
Keywords: Epic “Alpomish”, folklore language, simile, -day/-dek, linguopoetics, epic language, figurative device, axiological semantics.